Influence of Secondary Inorganic Aerosol on the Concentrations of PM2.5 and PM0.1 during Air Pollution Episodes in Hanoi, Vietnam - Nguyen-Quoc Dat; Bich-Thuy Ly; Trung-Dung Nghiem; Thu-Thi Hien Nguyen; Kazuhiko Sekiguchi; Truong-Thi Huyen; Thai-Ha Vinh; Le-Quang Tien (Aerosol and Air Quality Research)
Abstract The high concentration of PM2.5 in Hanoi has been an issue of great concern. There were several periods during the winter when PM2.5 concentrations were higher than the Vietnamese ambient air quality standards (NAAQS) and WHO guidelines for daily PM2.5. In this study, the periods when daily PM2.5 concentrations exceeded the NAAQS of 50 µg m−3 for a minimum of two consecutive days were determined as episode periods. The study focuses on the impact of secondary inorganic aerosol (SIA) on PM2.5 episodes in the dry winter period in Hanoi. To calculate SIA, water-soluble ions of daily PM2.5 and PM0.1 samples which were collected on the rooftop of a three-storeyed building at an urban site in Hanoi, Vietnam (HUST site) from October 14 to December 31, 2020, were analyzed. Levels and SIA of PM2.5 and PM0.1 at a transportation site (CEM site) in an episode period from December 20 to December 28, 2020 were also measured. The contribution of SIA on PM2.5 and PM0.1 during those episodes, the effects of meteorological conditions, and long-range transport were investigated. The results showed that SIA contributed on average 29.0% and 14.1%, respectively, to PM2.5 and PM0.1 concentrations during air pollution episodes at HUST. Those were higher than the average contribution percentages of total SIA to PM concentrations in non-episode periods for PM2.5 (25.6%) and PM0.1 (10.6%) at HUST. Among meteorological factors, wind speed largely affected PM2.5 concentration and SIA of PM2.5. Relative humidity, pressure, temperature, and radiation had a good correlation with SIA of PM0.1 and a moderate correlation with PM0.1. Concentration-weighted trajectory analysis demonstrated that PM2.5 and SIA levels were also influenced by long-range transportation from the upper areas. This study highlighted the importance and served as pioneered research on SIA contribution to PM2.5 episodes in the country.